Saksonia u boku Francji Napoleońskiej (1806-1813) = Saxony at the side of Napoleonnic France (1806-1813) - Jaworski, Tomasz (1944- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The period when Saxony appeared along with France, has had a significant impact on the strengthening of its endeavors to modernize both societies. Although full modernization process of them failed, Saxony ? regardless of everything ? economically strengthened and cemented its position as the Kingdom, even though it has suffered significant demographic and territorial losses, while the foundation of the Duchy of Warsaw emphasized that the decision of founding the favor dismantling treaties do not remove ?Polish case? of thinking about the future of Europe.
Keywords: Saksonia; Francja - historia - 19 w.; wojny napoleońskie - 1803-1815